Analisis Kepuasan Pelanggan Dalam Meningkatkan Kualitas Pelayanan Jasa Pada Kantor Notaris – PPAT Sulastri, S.H., M.Kn Di Kabupaten Klaten - Pujiastuti, Sekar Ayu; Yani, David Ahmad (Universitas Mitra Indonesia, 2025)
This study aims to determine how customer satisfaction improves the quality of service at the Notary Office - PPAT Sulastri, S.H., M.Kn in Klaten Regency. This study aims to improve service at the Notary Office - PPAT Sulastri, S.H., M.Kn to be better in the future and to determine the aspects that influence customer satisfaction in improving service at the Notary Office - PPAT Sulastri, S,H., M.Kn. The type of research used is qualitative description with data collection techniques using observation techniques, interviews and documentation studies. Data analysis techniques using the flow analysis model. The results of this study indicate that the quality of service at the Notary Office - PPAT Sulastri, S.H., M.Kn is quite satisfactory and in accordance with the services available, both making authentic deeds and making land deeds. The quality of service is acceptable to various groups because the employee's work steps can be understood when carrying out their duties, only there are some things that need to be fixed such as employee negligence due to the lack of customer files that hinder the process of files which automatically makes the service a little longer than the initial agreement.Keywords: Customer Satisfaction, Service Quality, and Service.